Hybridization: How Does a Waqf Institution Manage Its Complexity? Evidence from Yayasan Wakaf UMI - Iqbal, Muhammad; Sukmana, Raditya; Harymawan, Iman (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
This study aims to analyze the hybridization that occurs in waqf institutions. We combine a literature review, a case study, and expert opinions. The case study was conducted at the Indonesian Muslim University Waqf Foundation (YWUMI). Case study data collection was carried out through semi-structured interviews with 11 respondents. Requests for expert views were made through focus group discussions with four experts. Hybridization causes them to experience institutional complexity with the coexistence of business logic and Islamic social logic. YWUMI navigates institutional complexity through a structural differentiation strategy in which each unit of logic applies differently. In addition, the internalization of Islamic morality helps them manage organizational hybridity. The use of a hybrid organizational approach and institutional logic will provide insight into waqf management, especially regarding the institutional impact of initiatives to encourage productive waqf management.